How brand decisions for durable household goods are made at the bottom of the pyramid - Dlamini, Baleseng (My University, 2020)
The bottom-of-the-pyramid (BOP) market is a very large growing number of aspirational people, spread out all over the world, with Africa being the biggest BOP market in the world. This market presents a unique opportunity for companies wanting to increase their profits. However, companies have to be willing to take the risk in order to succeed and subsequently contribute to the global economy. The market is largely unexplored in Africa, and so there is a lack of academic research around consumer decision-making at the bottom-ofthe-pyramid. This market constitutes the majority of people living in South Africa and so this study was conducted to contribute to research in this sphere, and aid marketers operating in this market. The purpose of this study is to investigate how brand decisions for durable household goods are made by South Africa’s bottom-of-the-pyramid markets. The relationship between brand awareness, brand recall and brand recognition with purchase intention will be investigated. A survey method using a questionnaire was used for this study. People living in two South African townships, Soweto in Johannesburg and Soshanguve in Pretoria, were approached and 200 respondents were interviewed. Data was analysed using Confirmatory Factor Analysis and Structural Equation Modelling using SPSS and IBM Amos version 21. The results of the study showed that brand recall has a significant impact on consumer’s purchase intention, but brand awareness and brand recognition were found to have a negative relationship with consumer’s purchase intention. Recommendations for future studies were made - that other variables like brand image and brand associations, that could affect purchase intent, be interrogated. Also recommended is an alternative approach to assess discriminant validity.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Management in the field of Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Bottom-of-the-pyramid; Brands; South Africa; Brand awareness; Brand recall; brand recognition; SDG-8: Decent work and economic growth